Renewable energy support mechanisms in the Gulf Cooperation Council states: Analyzing the feasibility of feed-in tariffs and auction mechanisms. (May 2017) - Atalay, Yasemin; Kalfagianni, Agni; Pattberg, Philipp
Abstract: Renewable energy will be a crucial ingredient in the transition to a more sustainable future. The renewable energy sector requires a variety of financial support mechanisms in order to further consolidate and expand. Currently, the most prominent renewable energy support mechanisms are feed-in tariffs and renewable energy auctions. Although these mechanisms have been used and analyzed extensively in Western countries and, more recently, economies in transition, they have rarely been examined in the Arab Gulf region. Yet, particularly the Gulf Cooperation Council (GCC) states have undertaken important steps towards renewable energy adoption, which could be greatly facilitated with the use of financial support mechanisms. This paper analyzes the feasibility of feed-in tariffs and renewable energy auctions adoption in GCC. Based on an extensive meta-analysis of the literature on these two mechanisms in both developed and developing countries, the paper identifies a set of conditions necessary for success and evaluates the presence of favorable these conditions in the GCC context. Our findings reveal that while conditions that would ensure political feasibility are largely absent for both types of mechanisms, auctions could be a more successful strategy at the moment. Graphical abstract: Highlights: We observe lack of substantial renewable energy support mechanisms in GCC states. Feed-in tariff and auction policies of various countries are reviewed Three conditions for successful application were identified for each mechanism These conditions are not yet fully present in GCC countries Auctions are a more feasible strategy for GCC countries at the moment.